2000
DOI: 10.1016/s1074-7613(00)00016-9
|View full text |Cite
|
Sign up to set email alerts
|

ICSBP Directs Bipotential Myeloid Progenitor Cells to Differentiate into Mature Macrophages

Abstract: During hematopoiesis, myeloid progenitor cells give rise to granulocytes and macrophages. To study the role for ICSBP, a hematopoietic cell-specific transcription factor in myeloid cell development, the gene was introduced into myeloid progenitor cells established from ICSBP-/- mice. ICSBP retrovirus-transduced cells differentiated into mature macrophages with phagocytic activity, which coincided with the induction of specific target DNA binding activity. Similar to macrophages in vivo, ICSBP-transduced cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
304
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 280 publications
(322 citation statements)
references
References 49 publications
17
304
1
Order By: Relevance
“…IRF-8 Ϫ/Ϫ mice harbor an increased number of myeloid progenitor cells defective in the ability to differentiate to macrophages and consequently mature mainly to granulocytes. Accordingly, these IRF-8-deficient mice eventually develop a CML-like disease (6,12). In humans, 66% of AML and 79% of CML patients exhibit reduced levels of IRF-8 or no expression at all.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IRF-8 Ϫ/Ϫ mice harbor an increased number of myeloid progenitor cells defective in the ability to differentiate to macrophages and consequently mature mainly to granulocytes. Accordingly, these IRF-8-deficient mice eventually develop a CML-like disease (6,12). In humans, 66% of AML and 79% of CML patients exhibit reduced levels of IRF-8 or no expression at all.…”
Section: Discussionmentioning
confidence: 99%
“…CL-2 murine macrophage cell line and Tot2 myeloid progenitor cell line were derived from IRF-8 Ϫ/Ϫ mice and maintained as described previously (6,28).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A transcription factor that may be critical for determining the macrophage phenotype is IFN consensus sequence binding protein (ICSBP), an IFN-␥-inducible transcription factor specifically expressed in hemopoietic cells. ICSBP is required for the differentiation of myeloid progenitors into mature macrophages (41) and, in combination with IRF-1 and PU.1, regulates a number of IFN-␥-responsive genes. It is tempting to speculate that ICSBP may direct mature macrophages to differentiate further into a cell type that is required for TNF to suppress tumor growth.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, lack of IRF-8 was reported in human myeloid leukemias, implicating its pivotal role as a tumor suppressor gene (Schmidt et al 1998). Thus, IRF-8 drives bipotential myeloid progenitor cells towards mature macrophages while inhibiting the differentiation pathway towards granulocytes (Tamura et al 2000). In addition, it was shown that IRF-8 is an essential factor for proper functioning of mature macrophages.…”
Section: Interferon (Ifn) Regulatory Factor-8 (Irf-8) Also Known As mentioning
confidence: 99%